The Impact of COVID-19 Outbreak on the Power Sector in Bangladesh: A Strategic Adoption for Any Pandemic Condition - Ahmed, Kazi Firoz; Imroze, Rubaiyat; Faiz, Rethwan; Alam, Nuzat Nuary; Najibullah, Mohammad (AIUB Journal of Science and Engineering (AJSE), 2024)
In this research all the data sets were gathered during the COVID-19 outbreak. The study presented, however, is applicable to any pandemic scenario in Bangladesh or elsewhere. The lockdown has significantly reduced the demand for power worldwide and altered the makeup of the load and the daily load profile. This is because many offices have switched to home office strategy, which has shortened the operating schedule of many businesses. Considering this, many countries' adoption of lockdown measures to halt the spread of COVID-19 abruptly changed socioeconomic operations, including the power generation industries. To better understand the pandemic's impact on Bangladesh's fossil-fuel based power sector, this study examines renewable energy technologies' roles in creating climate resilient, sustainable energy routes. Research was done for the pandemic lockdown in 2020. Due to the lockdown situation, the power sector witnessed increased overcapacity, and revenue losses. This study looked at the implications on energy demand, load profiles, generation, consumption, generating mix, and expansion of renewable electricity generation. In addition, a suitable generation mix for Bangladesh has been suggested. This sector's resilience has also been assessed to overcome the pandemic crisis and any future pandemic-like emergency. In this research, a well-organized examination of the existing power sector overall plan has also been proposed, focusing on clean energy led power sector development.